Pengembangan Media Pembelajaran Interaktif Berbasis Android Pada Mata Pelajaran PJOK Untuk Siswa Kelas VII - Vika Fatikha Rahmawati; Hariyoko Hariyoko (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This study aims to develop interactive learning media based on android in physical education, sports and health subjects for class VII SMP Tamansiswa Malang with the help of Unity 3D software. This study used the Borg & Gall Research and Development method. The subjects used were all students of class VII SMP Tamansiswa Malang. For data collection instruments in the form of observation, by observing the process of learning activities directly on subjects of physical education, sports, and health on health material. This research was validated by physical education, sports and health learning experts, learning media experts, and physical education, sports and health teachers for class VII SMP Tamansiswa with a very decent category. Then the results of the overall product trial involving all VII grade students of Tamansiswa Malang Middle School were divided into two small group trials with a sample of 10 students obtaining 83.37% results and large group trials with all VII grade students obtaining 95.34% results so very worthy. Based on the data that has been obtained, it can be concluded that the android-based interactive learning media developed for class VII students of SMP Tamansiswa Malang is categorized as very feasible and can be used without revision.